Stories from Berea College : opportunities of attending a work college - Hartlep, Nicholas Daniel; Stanton, Breyden (Emerald Publishing Limited : IAP | Information Age Publishing, Inc., 2022)
"This book was born during the Omicron surge of the COVID-19 pandemic. While it is uncertain what the pandemic will hold, one thing is for certain, this book will stand the test of time. Work Colleges do not receive the scholarly attention they ought to, and the student authors would like to think they fought for a little more attention by writing this book. Work Colleges are indeed institutions of higher learning where students earn while they learn, but also learn through hard work. This book is comprised of chapters written by students who discuss the magic Berea College holds for personal growth, opportunity, and life changing experiences"--